The values identity in the professor's of Biology initial formation - Ibrahin Clavel-Hernández; Eumelia Victoria Romero-Pacheco; Yolanda Shum-Hung (Maestro y Sociedad, 2016)
The formation of professionals of the education in Cuba is characterized to be a process in continuous improvement. This is important for the achievement of an education that not guarantees alone the acquisition of knowledge, but also the development of attitudes, values and feelings in children and young. The professor's of Biology initial formation should prepare them integrally to direct in an efficient way the process of teaching-learning of this subject in the secondary education and also, to develop in the student the commitment of to conserve and to make sustainable use of the natural resources that are related and they characterize its environmental partner. From this formation process the education should be assisted in values and like essential part of this. The attribution of meanings that each individual grants to the components of the ecosystem in that is related at the same time that it incorporates them like part of this identity.